2015
DOI: 10.1002/ajh.24182
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for myelofibrotic transformation among 272 Chinese patients with JAK2-mutated polycythemia vera

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as an 'Accepted Article', doi: 10.1002/ajh.24182This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…MPNs mainly include polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) . Thrombosis, leukemic transformation, and myelofibrotic transformation are critical complications of MPN and are highly common in patients with MPN . Fatalities due to thrombosis account for 35%~70% of the total mortality rate of MPN, making it the most important risk factor affecting event‐free survival and overall survival (OS) of MPN patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPNs mainly include polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) . Thrombosis, leukemic transformation, and myelofibrotic transformation are critical complications of MPN and are highly common in patients with MPN . Fatalities due to thrombosis account for 35%~70% of the total mortality rate of MPN, making it the most important risk factor affecting event‐free survival and overall survival (OS) of MPN patients …”
Section: Introductionmentioning
confidence: 99%
“…1 Thrombosis, leukemic transformation, and myelofibrotic transformation are critical complications of MPN and are highly common in patients with MPN. [2][3][4][5][6] Fatalities due to thrombosis account for 35%~70% of the total mortality rate of MPN, making it the most important risk factor affecting eventfree survival and overall survival (OS) of MPN patients. 7 Studies in the last decade have shown that JAK2/CALR/MPL gene mutations are the driver mutations in MPN.…”
Section: Introductionmentioning
confidence: 99%
“…When we combined risk levels to establish a range of possible OS levels, our model provided an OS range of 14.2 to 17.3 LY depending on age and baseline JAK2. Only the study by Bai et al 19 had an OS (17.5 LY) that slightly fell outside of the modeled OS range.…”
Section: Discussionmentioning
confidence: 82%
“…We developed an economic model for PV that combines data from multiple sources such as clinical trials and long-term observational cohort studies. 12,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] The objective of this study was to validate the model that uses JAK2 burden as a surrogate endpoint to predict DP and OS based on progression-specific mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation